Measurement of Passenger Expectations and Satisfaction Toward The Integrated Mode Transfer Service of Suroboyo Bus - Ira Niluh Rinjani; Hera Widyastuti (Universitas Islam Raden Rahmat, Malang, 2026)
Interconnected public transportation plays an essential role in facilitating community mobility, especially in ensuring seamless mode transfers at integrated locations. This study aims to evaluate passengers’ expectations and satisfaction toward the integration of mode transfer services in the Suroboyo Bus public transportation system. The research was conducted at five main integration stops, namely Joyoboyo Intermodal Terminal (TIJ), Purabaya Terminal, Dukuh Menanggal Bus Stop, Marmoyo Bus Stop, and UINSA Bus Stop. The analytical methods employed in this study are the Customer Satisfaction Index (CSI) and the Importance Performance Analysis (IPA). Primary data were obtained from 250 respondents through questionnaire distribution, with the sample size determined using the Slovin formula. The results show that the CSI score of 78,16% indicating that the passengers' satisfaction level falls within the satisfied category. However, the IPA results indicate a gap between expectations and satisfaction across all indicators, with eight attributes emerging as priority areas for improvement. Therefore, it can be concluded that the integration of mode transfer services in the Suroboyo Bus system has generally met passengers’ expectations, although further improvements remain necessary to ensure a more optimal and inclusive travel experience for all users.